Malignant solitary fibrous tumor in the extremity: Cytopathologic findings - Khanchel, Fatma (Medknow Publications & Media Pvt Ltd, 2012)
Malignant solitary fibrous tumor (SFT) is an extremely rare neoplasm. There are only rare published accounts of the cytopathologic features of this tumor. We report a case of a 59-year-old woman presented with a 10-year history of a right thigh mass. A preoperative fine needle aspiration (FNA) was performed. Smears were hypercellular, with cohesive and crowded tissue fragments, haphazard cell arrangements and many single cells. The tumor cells were polymorphous, plump spindled or round with often indented or bare nuclei. A differential diagnosis of low grade sarcoma was favored. The diagnosis of malignant SFT is extremely difficult on FNA and must be included in the differential diagnosis of spindle cell neoplasms.